Propeller Flaps in the Head and Neck - Cordova, Adriana; D'Arpa, Salvatore; Rosatti, Fernando; Nichelini, Marta; D'Antonio, Giovanni Maria; Giordano, Salvatore; Toia, Francesca (Seminars in Plastic Surgery, 2020)
Propeller flaps have significantly expanded the reconstruction possibilities in the head and neck region. They allow for increased flap mobility and better scar concealing, and/or to perform a one-stage reconstruction with local tissue of similar color and texture, where multiple surgeries would be needed with traditional flaps or even free flaps would be required. This article describes the main propeller flaps for one-stage reconstruction in the head–neck region (facial artery perforator, supratrochlear artery axial perforator, deep lingual artery axial perforator, and anterior supraclavicular artery perforator flaps), their indications, and possible complications. Aesthetic and functional results of propeller flaps in the head and neck region are very good and the complication rate is low, but due to their surgical complexity and the availability of many simpler local flaps, they are indicated only in select cases where local flaps are unavailable or would require multiple staged procedures to complete the construction.
Keywords: head and neck reconstruction; perforator flaps; propeller flaps; facial artery perforator; supratrochlear artery perforator; supraclavicular artery perforator; lingual flaps